Courtship in Japan and Iceland. Then and Now - Thelma Rún Heimisdóttir 1992- (2015)
The aim of this thesis is to examine and compare the ritual of courtship and dating in Iceland and Japan in modern times and how they relate to each other i.e. similarities and differences. This thesis will attempt to give a general overview of the history of courtship, marriage and dating around the world to explain the general background of each term. The thesis discusses the history of courtship and marriage in Iceland and Japan to learn the differences and similarities between those two cultures during history as well as today and how it has evolved into modern dating. In order to attain the best research possible, miscellaneous literature sources were used as well as several interviews were conducted.